Perbaikan Postur dan Fasilitas Kerja Menggunakan Metode Biomekanika dan Niosh Pada PT XYZ - Hernanda Bambang Sugiarto; Surya Perdana (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2024)
PT XYZ is a private company engaged in freight forwarding, there are several problems that cause its workers to experience discomfort in special body areas caused by non-optimal work positions and lack of adequate facilities in the loading and unloading process. The purpose of this study was to determine the dominant injuries experienced by workers, proposals for improving work posture, and proposed facility designs for loading and unloading workers. The methods used Biomechanics and NIOSH with the help of 3D SSPP applications. This study examines the posture of workers, proposals for improving work posture, and proposals for the design of work facilities. This research was conducted because there were complaints from workers who often experienced injuries. From the results of this study, it was found that the most common injuries experienced by workers who carry out loading and unloading are in the back area and the lower part of the arm. The results of improved suggestions related to work posture show that the resulting angle is 50 degrees on the palm, 43 degrees on the forearm, 58 degrees on the upper arm, 49 degrees on the back, 57 degrees on the abdomen, and 21 degrees on the thigh can reduce the risk of injury. In addition, the proposed improvement of facilities is that the use of hand trolleys can also reduce the risk of injury and can increase worker productivity.